2010
DOI: 10.3233/thc-2010-0577
|View full text |Cite
|
Sign up to set email alerts
|

Climate chamber for environmentally controlled laboratory airflow experiments

Abstract: Climate chambers have been widely used in in vitro and in vivo studies which require controlled environmental temperature and humidity conditions. This article describes a new desktop climate chamber that was developed for application of respiratory airflows on cultured nasal epithelial cells (NEC) under controlled temperature and humidity conditions. Flow experiments were performed by connecting the climate chamber to an airflow generator via a flow chamber with cultured NEC. Experiments at two controlled cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…In addition, it was shown that tracheal and nasal mucociliary beat frequency decreases as the temperature falls below 20°C and totally ceases at 5°C ( 72 ). These studies indicate that low temperature and low humidity in the nasal airway compromise the MCC by increasing mucin secretion and reducing mucociliary beat frequency ( 67 , 71 , 73 ). Moreover, a study done on guinea pigs revealed that breathing dry air can disrupt cilia, damage epithelial cells, and induce local inflammation of the trachea ( 74 ).…”
Section: Drivers Of Seasonality Of Respiratory Virusesmentioning
confidence: 92%
See 2 more Smart Citations
“…In addition, it was shown that tracheal and nasal mucociliary beat frequency decreases as the temperature falls below 20°C and totally ceases at 5°C ( 72 ). These studies indicate that low temperature and low humidity in the nasal airway compromise the MCC by increasing mucin secretion and reducing mucociliary beat frequency ( 67 , 71 , 73 ). Moreover, a study done on guinea pigs revealed that breathing dry air can disrupt cilia, damage epithelial cells, and induce local inflammation of the trachea ( 74 ).…”
Section: Drivers Of Seasonality Of Respiratory Virusesmentioning
confidence: 92%
“…The nasal respiratory epithelium is made up of ciliated cells covered with an airway surface layer comprised of a mucus layer that catches inhaled particles and low viscosity pericilliary layer that moisturizes the surfaces and enable ciliary beating (70). MCC is a key mechanism required for getting rid of particles, including infectious agents, stuck on the surface of the respiratory epithelium (70). Production of thin mucosal layer and beating of cilia at a specific frequency are considered key factors for efficient MCC (66).…”
Section: Effect Of Meteorological Factors On Host's Susceptibility Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, cold (18°C) exposure or menthol treatment of cultured NHBE cells increases MUC5AC secretion in a TRPM8-dependent manner (82,83). Another study examined the effect of temperature, humidity, and airflow mimicking respiration on mucin secretion from human nasal epithelial cells using a climate chamber for cell culture (84). Mucin production increased under 25°C, 40% RH compared to 37°C, 80% RH.…”
Section: Mucus Productionmentioning
confidence: 99%
“…By virtue of being exposed to ambient air by breathing, the nasal and tracheal mucosal surface of the respiratory tract is affected by ambient temperature and the water content of the inhaled air (74). Inhalation of dry air causes epithelial damage, MCC impairment, and increased mucin production (84,87,88). Impaired ISG expression and tissue repair and increased viral burden and mortality after influenza virus infection have been proven in mice exposed to 7 days of low RH of 10-20% (88).…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%